2021
DOI: 10.1177/14614448211020752
|View full text |Cite
|
Sign up to set email alerts
|

Engineering care in pandemic technogovernance: The politics of care in China and South Korea’s COVID-19 tracking apps

Abstract: This article critically examines South Korea and China’s COVID-19 tracking apps by bridging surveillance studies with feminist technoscience’s understanding of the “politics of care”. Conducting critical readings of the apps and textual analysis of discursive materials, we demonstrate how the ideological, relational, and material practices of the apps strategically deployed “care” to normalize a particular form of pandemic technogovernance in these two countries. In the ideological dimension, media and state d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 35 publications
2
18
0
Order By: Relevance
“…The very divergence can imply (un)expected marginalization of certain populations for both “too little privacy” and “too much privacy” ( Gilman & Green, 2018 ). Most recent studies on COVID-19 tracking apps/algorithms in Asian countries have suggested such a relational turn to the understanding of digital contact tracing as a surveillance technology ( Kim et al, 2021 ; Liu & Graham, 2021 ), and the need for relational examination of surveillance technologies is not and should not be limited to a particular culture (e.g., collectivist vs. individualistic cultures). Our study identified patterns of both “care” and “concern” for community members together with institutional (dis)trust and ongoing privacy concerns in the US context that is not generally deemed a collectivist culture.…”
Section: Discussion: the Relational Turn Of Surveillance Technology I...mentioning
confidence: 99%
See 1 more Smart Citation
“…The very divergence can imply (un)expected marginalization of certain populations for both “too little privacy” and “too much privacy” ( Gilman & Green, 2018 ). Most recent studies on COVID-19 tracking apps/algorithms in Asian countries have suggested such a relational turn to the understanding of digital contact tracing as a surveillance technology ( Kim et al, 2021 ; Liu & Graham, 2021 ), and the need for relational examination of surveillance technologies is not and should not be limited to a particular culture (e.g., collectivist vs. individualistic cultures). Our study identified patterns of both “care” and “concern” for community members together with institutional (dis)trust and ongoing privacy concerns in the US context that is not generally deemed a collectivist culture.…”
Section: Discussion: the Relational Turn Of Surveillance Technology I...mentioning
confidence: 99%
“…While horizontal surveillance systems may not be always voluntary, these studies speak to the social aspects of surveillance technologies individuals consider. Recent studies on diverse forms of contact-tracing systems in China and South Korea have found that people often approve these technologies to “care for” and “protect” others in the community ( Kim et al, 2021 ; Liu & Graham, 2021 ).…”
Section: Surveillance Technologies In Horizontal and Vertical Termsmentioning
confidence: 99%
“…Although social media can facilitate greater access to diverse information and boost online political participation ( Diamond 2015 ; Enikolopov et al 2020 ), recent studies have also highlighted that governments in different national contexts utilize social media for early warnings of natural disasters and disease control during crises ( Chatfield et al 2013 ; Kim et al 2021 ). Moreover, governments in authoritarian contexts have increasingly been using social media to mobilize content for publicity and to maintain state stability ( King et al 2013 ; Schlæger and Jiang 2014 ).…”
Section: Political Information Seeking From Government Social Media A...mentioning
confidence: 99%
“…And a focus on mental health surveillance and service provision reveals a strong element of (paternalistic) “care” at the heart of the Chinese approach to COVID surveillance (c.f. Kim et al, 2021 , for a feminist critique of the notion of care through surveillance).…”
mentioning
confidence: 99%